Avaliação da atividade de formulações comerciais de repelentes sobre mosquitos Aedes aegypti (Diptera - Culicidae) - Estevam, Adriana dos Santos (2018)
Objectives: To evaluate the efficacy of commercially used insect repellents against Aedes aegypti stings. Material and Methods: Was used method standard the World Health Organization to evaluate the sensitivity of the mosquito by estimating the total protection time (TPT) of the repellent. The test consists of application of the product and introduction of the volunteer arm into cages containing 50 female mosquitoes, aged between five and seven days. The initial product was 10% technical grade N, N diethylbenzamine (DEET) and four formulations with different concentrations of DEET, OFF Family (7,125%), Baruel (9,5%), Expert Total : 1612043 and 16144314, Super Repelex Aerosol (11%), product based on IR3535 (Repeden Spray 12%, Jonsons Baby Lotion 12.5%), and the ICARIDINE base (Exposis Extreme Tetra 25%), by the median of each product in 6 volunteers, being three men and three women. Results: The OFF Family brand (DEET 7,125%), Baruel (DEET 9,5) and analytical DEET (10%) demonstrated a median of 30 minutes, even presenting different concentrations; Super Repelex Aerosol (DEET 11%) among the products containing DEET was the one that presented a higher median, with a TPT of 90 minutes; Expert Total (DEET 15%) (1st batch) and Expert Total (DEET 15%) (2nd batch) are shown with medians equal with a time of 60 minutes; Repeden Spray (IR3535 12%) and Johnsons baby (IR3535 12.5%) presented a median TPT of 60 and 30 minutes respectively, differing only in the degree of concentration of the active principle; Exposis Extreme (25% Icaridina) presented a median of 120 minutes, showing a superiority in relation to the other products. Conclusion: The products had a complete protection time lower than the one specified in their labels, and may leave the population that use them as a control measure against several unprotected diseases, requiring a greater number of reapplications of the products.